Proposed upgrading interior design scheme of arts centre for Five Arts Centre at 27 & 29 Lorong Datuk Sulaiman 7, Taman Tun Dr Ismail, 6000 Kuala Lumpur, Selangor / Muhammad Asyraf Abdul Razak - Abdul Razak, Muhammad Asyraf (Faculty of Architecture, Planning and Surveying, 2012)
The project is an upgrading project for Five Arts Centre at 27 & 27a Lorong Datuk Sulaiman 7, Taman Tun Dr Ismail, 6000 Kuala Lumpur, Malaysia. Five arts centre serves as a collective of artists and producers to generate alternative art forms and images in the Malaysian creative environment. In order to reach out to their audience and community Local artist must know how to interect and shares knowledge, skills and talents wether in theatre, dance, music, visual arts and young people's theatre. The issues are they lack of exposure to the community and the building does not have a quality image where an art centre should be. The project aim is to provide suitable spaces with new facilities and new image. Which can provide more platforms for the next generation of art practitioners. Furthermore it can satisfy their work and passion in art in a better way at the same time bring knowledge for community about local Malaysian theatre and Malaysian culture. The objectives for the project is to give a new environment in terms of image and style, to create a new space planning, promote the art centre to Malaysians and give opportunity for community to participate and understand local art scene in terms of theater and musical play. At the same time to give opportunities for talented artists in highlight their talent to communities.